SHAPING ECOLOGICALLY FOCUSED WORLDVIEW IN EDUCATION: THEORETICAL APPROACHES - Natalia V. Levchenko (National Research Mordova State University, 2016)
Introduction: this article is an analysis of scholarly publications, that elaborates on the necessity of teaching environmental education through various forms. The study reveals the complementary relationship between formal and informal education. A number of theoretical approaches to the study of formation of ecologically focused worldview that can be applied to environmental educatio n in modern Russia is considered. Materials and Methods: the works of scholars who used systemic, synergetic and competence-based approaches were used to write this paper, axiological and eco-centric approaches are considered in view of the fact that the eco-centric worldview and axiological approach is directly related to the category of “value”. The article examines a number of publications on this topic. Results: the analysis of scholarly literature has shown that the main characteristics of formal and informal environmental education, the process of forming a system of values and world views are seriously discussed in the framework of various theoretical and methodological appr oaches. Discussion and Conclusions: analysis of publications allows to conclude that sociology is not paying enough attention to environmental education and especially environmental outreach activities carried out by university professors, staff of the environmental non-profit organisations and specially protect¬ed areas. Research shown that the task of environmental education representatives is not only in the formation of ecological culture of the population, but also in defense of the values that contribute to the environmentally oriented development of modern civilisation. In view of the fact that the problems associated with environmental risks are cumulating, one should focus fully on specifics of environmental education in a society .